Modernization of Shot Blasting Procedure - Bukantaitė, Simona; Čikotienė, Dalia (Jaunųjų mokslininkų darbai, 2018)
Every company has the intention to produce the best quality product and get the highest profit. In the 21st century, it has become much harder to stay competitive because consumers have a large selection of equivalent goods. This article analyses company’s X growth in reference to the shot blasting process in order to investigate if modernization is feasible. Tests of shot blasting work place safety were carried out and all information submitted in a professional risk identification card. Calculations were made to investigate if the robotisation is profitable. Virtual simulation of robotic line was created with Visual Components software.
Keywords: modernization; shot blasting; robotisation; virtual manufacturing; Visual Components